Patterns of Retinal Ganglion Cell Damage in Neurodegenerative Disorders: Parvocellular vs Magnocellular Degeneration in Optical Coherence Tomography Studies - La Morgia, Chiara; Di Vito, Lidia; Carelli, Valerio; Carbonelli, Michele (Frontiers in Neurology, 2017)
Many neurodegenerative disorders, such as Parkinson’s disease (PD) and Alzheimer’s disease (AD), are characterized by loss of retinal ganglion cells (RGCs) as part of the neurodegenerative process. Optical coherence tomography (OCT) studies demonstrated variable degree of optic atrophy in these diseases. However, the pattern of degenerative changes affecting the optic nerve can be different. In particular, neurodegeneration is more evident for magnocellular RGCs in AD and multiple system atrophy with a pattern resembling glaucoma. Conversely, in PD and Huntington’s disease the parvocellular RGCs are more vulnerable. This latter pattern closely resembles that of mitochondrial optic neuropathies, possibly pointing to similar pathogenic mechanisms. In this review, the currently available evidences on OCT findings in these neurodegenerative disorders are summarized with particular emphasis on the different pattern of RGC loss. The optic nerve degeneration could become a validated biomarker of the disease, which may turn useful to follow natural history and possibly assess therapeutic efficacy.